Analysis of Mathematical Connection Ability Based on Independent Character in Project Based Learning Assisted With Digital Module - Kusnandar, Kusnandar; Junaedi, Iwan; Suyitno, Amin (Unnes Journal of Mathematics Education Research, 2021)
The purpose of this study is to describe the students' mathematical connection ability based on their independent character in Project Based Learning assisted with digital module. The study was conducted using a qualitative method with the research subjects are students of grade XI TAV 1 SMK Negeri 1 Kandeman in the 2019/2020 academic year as many as 36 people. The data were collected by using questionnaire, observation, documentation, and interviews. The data analysis was conducted by data reduction, data display, triangulation, data interpretation, and data conclusion. The result show that the students' independent character has two categories, namely very independent and independent. Students’ mathematical connection ability are varied for both independent character category.